Reduced Glutathione Promoted Growth Performance by Improving the Jejunal Barrier, Antioxidant Function, and Altering Proteomics of Weaned Piglets - Zhimei Tian; Yiyan Cui; Miao Yu; Dun Deng; Zhenming Li; Xianyong Ma; Mingren Qu (Antioxidants)
Reduced glutathione (GSH) is a main nonenzymatic antioxidant, but its effects and underlying mechanisms on growth and intestinal health in weaned piglets still require further assessment. A total of 180 weaned piglets were randomly allotted to 5 groups: a basal diet (CON), and a basal diet supplemented with antibiotic chlortetracycline (ABX), 50 (GSH1), 65 (GSH2), or 100 mg/kg GSH (GSH3). Results revealed that dietary GSH1, GSH2, and ABX improved body weight and the average daily gain of weaned piglets, and ABX decreased albumin content but increased aspartate aminotransferase (AST) activity and the ratio of AST to alanine transaminase levels in plasma. GSH2 significantly decreased glucose content but increased the content of triglyceride and cholesterol in the plasma. Both GSH1 and GSH2 improved the jejunal mucosa architecture (villus height, crypt depth, and the ratio of villus height to crypt depth), tight junction protein (ZO-1 and Occludin), and antioxidant capacity (CAT and MDA), and the effects were superior to ABX. Dietary GSH improved the jejunal barrier by probably inhibiting the myosin light chain kinas pathway to up-regulate the transcript expression of tight junction protein (ZO-1 and Occludin) and Mucins. Through the proteomics analysis of the jejunal mucosa using 4D-DIA, the KEGG pathway enrichment analysis showed that differentiated proteins were significantly enriched in redox homeostasis-related pathways such as glutathione metabolism, cytochrome P450, the reactive oxygen species metabolic pathway, the oxidative phosphorylation pathway, and the phosphatidylinositol 3-kinase-serine/threonine kinase pathway in GSH2 vs. CON and in GSH2 vs. ABX. The results of proteomics and qRT-PCR showed that GSH supplementation might dose-dependently promote growth performance and that it alleviated the weaning stress-induced oxidative injury of the jejunal mucosa in piglets by activating SIRTI and Akt pathways to regulate GPX4, HSP70, FoxO1. Therefore, diets supplemented with 50–65 mg/kg GSH can promote the growth of and relieve intestinal oxidative injury in weaned piglets.